Haematological parameters and serum trace elements in "healthy" and "unhealthy" morbidly obese patients before and after gastric bypass. Issue 2 (April 2015) - Ferrer, Roser; Pardina, Eva; Rossell, Joana; Baena-Fustegueras, Juan Antonio; Lecube, Albert; Balibrea, José María; Caubet, Enric; González, Oscar; Vilallonga, Ramón; Fort, Jose Manuel; Peinado-Onsurbe, Julia
Summary Background & aims We have investigated the differences in plasma parameters and serum trace elements between "healthy" and unhealthy morbidly obese patients before and after Roux-en-Y gastric bypass surgery. Methods A group of 32 morbidly obese patients undergoing bariatric surgery were divided into three groups. Group 1 subjects were free of dyslipidemia and type II diabetes mellitus (defined as "healthy" obese, DM−DL−); Group 2 subjects had only the presence of dyslipidemia (DM−DL+), while group 3 patients demonstrated the presence of both (DM + DL+). In all patients, we studied haematological, haemostasis, anaemia, coagulation plasma and trace elements parameters before and 1, 6 and 12 months after gastric bypass surgery. Results We found significant differences in some haematological parameters, including haemostasis (e.g., T-Quick, p = 0.0048) and coagulation (e.g., ATIII and PAI-1, p = 0.001 and p < 0.0001, respectively) and in anaemia parameters (e.g., folate, cobalamin and transferrin, p = 0.0002, p < 0.0001 and p = 0.0001, respectively) but also in serum trace elements between the groups. However, the response to bariatric surgery was similar in the three groups. Conclusion Any healthy morbid obese subject is really metabolically "unhealthy" because he or she has many other haematologic or serum abnormalities that are often not included in the criteria for the definition of "healthy" in these obese subjects.